Bifurcation Analysis of Fractional Order Single Cell with Delay - Celik, Vedat (World Scientific Publ Co Pte Ltd, 2015)
This paper presents the bifurcation analysis of fractional order model of delayed single cell which is proposed for delayed cellular neural networks with respect to the time delay tau. The bifurcation points, time delay tau(c), are determined by modified Mikhailov stability criterion for a range of fractional delayed cell order 0.3 <= q < 1. Numerical results obtained from Adams-Bashforth-Moulton method demonstrate that the supercritical Hopf bifurcation occurs in the system.
Keywords: Bifurcation; fractional order delayed cell; the modified Mikhailov stability criterion; limit cycle